Terras de cavaleiros geopark: a UNESCO global geopark - Pereira, D. I. (2020)
The Terras de Cavaleiros Geopark (TCG), a UNESCO Global Geopark, is located in Northern Portugal and is established on rare and unique geological, scenic, ecological and cultural values. The most significant geological value is related to the most complete sequence of Pre-Mesozoic allochthonous geological units in NW Iberia. The Vilariça fault is an important geomorpholog- ical feature in the TCG related to the evolution of landforms such as push-up blocks and strike-slip basins. Forty-two geosites were selected in the TCG, 16 of them being of geomorphological interest. A set of programs, including cultural heritage, biodiversity and leisure, has been prepared for scientific, educational and touristic use